Genus Triplaris (Polygonaceae): A review on traditional medicinal use, phytochemistry and biological activities. (15th September 2021) - Macêdo, Sandra Kelle Souza; Lima, Kátia Simoni Bezerra; Silva, Naiane Darklei dos Santos; Campos, Sírley Sharliny Gomes; Araújo, Bruna Rodrigues; Almeida, Jackson Roberto Guedes da Silva; Rolim, Larissa Araújo; Nunes, Xirley Pereira
Abstract: Ethnopharmacological relevance: The genus Triplaris (Polygonaceae) comprises approximately 25 species distributed throughout South and Central America. Some species have been used in folk medicine, mainly, to treat malaria, leishmaniasis, diarrheia, dysenteria, pain and inflammation. Aim of the study: The purpose of this review is to provide information on the traditional uses, phytochemistry and known biological activities of Triplaris, an important genus for South America research groups on medicinal plants, in order to explore its therapeutic potential to direct future research in the search for new bioactive molecules. Materials and methods: The available information on the genus Triplaris was gathered from scientific databases (LILACS, Pubmed, SciELO, Science Direct, Scopus, CAPES Periodicals Portal and Theses and Dissertations Catalog) before March 2020 using the keyword " Triplaris ". Works related to traditional uses, phytochemistry and biological activities of plants were included in this review. Results: Most of the studies involving Triplaris were conducted by research groups located in Brazil, Peru e Bolivia. Probably, because the genus has been used in folk medicine only by these countries. Regarding the annual evolution of the publications, a larger number of articles published in 2010 were observed. Flavonols represent the main classe of secondary metabolites from Triplaris . In terms of the pharmacological investigations, T. americana and T. gardneriana are considered the most studied species, with extensive promising biological activities. The pharmacological activities can be attributed to bioactive phytochemicals. Conclusions: All findings indicate that Triplaris is an important genus of the Polygonaceae family. However, considering its chemical and pharmacological importance, the studies developed with Triplaris species are still limited, representing an opportunity to investigate new bioactive molecules and extracts. The review shows that little pre-clinical or in vivo research is available to prove the ethnopharmacological records in the genre. Therefore, this review encourages further studies on Triplaris i n the search for a wide range of therapeutic products. Graphical abstract: Image 1 Highlights: The genus Triplaris has long been used in folk medicine in Peru, Bolivia and Brazil. Flavonols are the chemical markers of Triplaris. Extracts and/or compounds from Triplaris exhibited promising biological activities. Triplaris have been used mainly in the treatment of malaria, leishmaniasis, diarrhea, dysentery, pain and inflammation. The most studied species were T. americana and T. gardneriana.